Pengaruh Media dan Umur Biakan Jamur Metarhizium anisopliae M. terhadap Tingkat Kematian Larva Oryctes rhinoceros L. (Scarabaeidae ; Coleoptera) - UTARI, NI MADE WINDA; SUDIARTA, PUTU; BAGUS, I GUSTI NGURAH (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.4, No.2, April 2015, 2015)
ABSTRAK Influence of Medi a and F ungus Metarhizium anisopliae M. Age c ulture to Larvae Mortality of Oryctes rhinoceros L. ( Scarabaeidae; Coleoptera ) Oryctes rhinoceros L. is importance pest that can be serious problem to coconut plantations. The utilization of fungus Metarhizium anisopliae M. as biological agents has became a recommended alternative choice considering its selective and safe infect to ecosystem. The purposes of this study in order to find out the effectiveness rates of media and culture age of fungus M. anisopliae on   O. rhinoceros larvae mortality and to find out the culture age of M. anisopliae in corn and rice media that cause O. rhinoceros larvae mortality. This study used in vitro and direct trial method. The result showing that fungus Metarhizium anisopliae in culture age of 4 weeks have ability to infect the larvae since 6 th and on  14 th days after application the all of  larvae was infected. On the other hand the fungus in culture age of 3 weeks the  larvae was infected since 7 th day after application and on 21 st days after application the all larvae was infected. Keywords: , Oryctes rhinoceros L. Metarhizium anisopliae M.